Khyad chos bsre ʼphoʼi sa bcad naʼro ta paʼi źal gyi luṅ źes bya ba bźugs so - Padma-dkar-po, ʼBrug-chen IV, 1527-1592 (s.n., 1970)
Outline of the Bsre ʼpho, esoteric teaching setting forth the principles of tantric Buddhist hathayoga and the Na-ro chos drug.